ANALYSIS OF EFFECT OF PROBABILITY AND FIRM SIZE ON INTRINSIC VALUE WITH FINANCIAL DISTRESS AS AN INTERVENING VARIABLE IN OIL AND GAS COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Naibaho, Jahoras Victor; Khaira Amalia Fachrudin; Iskandar Muda (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to determine and analyze effect of probability and firm size on intrinsic value with financial distress as an intervening variable in Oil and Gas Companies on the Indonesian Stock Exchange. This research uses a quantitative type of research that is causal. Population in this study are 33 companies operating in Oil and Gas Sector which are listed on the Indonesia Stock Exchange which regularly report their financial reports to the Indonesia Stock Exchange from 2019 to 2021. Samples used in the research were 27 Oil and Gas Sector Companies on the Indonesian Stock Exchange. This research uses path analysis in structural equation modeling. The research results show that profitability has a positive and insignificant effect on intrinsic value in Oil and Gas Companies on the Indonesian Stock Exchange. Firm size has a positive and significant effect on intrinsic value in Oil and Gas Companies on the Indonesian Stock Exchange. Profitability has a negative and significant effect on financial distress in Oil and Gas Companies on the Indonesian Stock Exchange. Firm size has a positive and significant effect on financial distress in Oil and Gas Companies on the Indonesian Stock Exchange. Financial distress has a positive and insignificant effect on intrinsic value in Oil and Gas Companies on the Indonesian Stock Exchange. Profitability does not has an indirect effect on intrinsic value through financial distress in Oil and Gas Companies on the Indonesian Stock Exchange. Firm Size has an indirect effect on intrinsic value through financial distress in Oil and Gas Companies on the Indonesian Stock Exchange.